Proceedings of the Forum: Inequality and Social Mobility in the Digital Age (Revista Investigación & praxis en CS Sociales, 2025)
The presentation, delivered at the forum "Inequality and Social Mobility in the Digital Age," analyzed how territories are facing structural challenges of inequality in a global context of rapid digital transformation. From the GIT Research Group (Integrated Territorial Management) at the University of Pamplona and a project on early warning systems, the speaker addressed the social implications of technological progress, highlighting the transition from Industry 1.0 to 5.0 within a VUCA and BANI environment. Multiple challenges were identified: global risks such as income inequality, forced migration, and unemployment; structural crises such as extractivism, social exclusion, and gaps in access to science and technology; and deep inequality in Latin America, particularly in Colombia, where 1% of the population controls 80% of the land, 15% lives in extreme poverty, and the education system shows high dropout rates. Additionally, low social mobility was evident due to the intergenerational transmission of poverty. Finally, the presentation examined Colombia’s weak position in innovation (ranked 67th globally in 2021), emphasizing the need to strengthen the knowledge-based economy to address these challenges.
Keywords: Digital Divide; Social Mobility; Neuroeducation; Post-conflict; Territorial Challenges